Endophytic fungi as promoters of vegetative growth in nursery-grown grapevines - Rosas-Martínez, Jefferson; León-Ttacca, Betsabe; Álvarez-Bernaola, Luis A. (Bioagro, 2025)
Endophytic fungi are organisms that can promote growth and resistance to abiotic stresses in plants. The objective of this study was to evaluate the effect of various endophytic fungi on the vegetative growth of the 'Salt Creek' vine rootstock at nursery conditions. Fourteen fungal strains plus a non-inoculated control were evaluated to constitute a trial with 15 treatments and 4 repetitions under a completely randomized design. The strains with concentration of 1×106 ufc·g-1 were inoculated every 15 days on the plants, and measurements of growth were made after 105 days. The results indicated that the Aspergillus niger strain outperformed the vast majority of strains, except for Trichoderma inhamatum and Cladosporium halotolerans, with which it shared statistical significance in the variables of shoot length and diameter, root length, and aerial biomass, and with T. asperellum and Penicillium steckii in the variable of total biomass. In the root biomass, the highest averages were found in two strains of T. asperellum. It is concluded that the strains of A. niger, T. inhamatum and C. halotolerans are the ones that best promote the vegetative growth of the vine rootstock in its initial stages, while demonstrating very good potential for its application in crops for sustainable agriculture.